2017
DOI: 10.2147/opth.s145159
|View full text |Cite
|
Sign up to set email alerts
|

Bilberry extract administration prevents retinal ganglion cell death in mice via the regulation of chaperone molecules under conditions of endoplasmic reticulum stress

Abstract: PurposeTo investigate the effect of bilberry extract anthocyanins on retinal ganglion cell (RGC) survival after optic nerve crush. Additionally, to determine details of the mechanism of the neuroprotective effect of bilberry extract anthocyanins and the involvement of endoplasmic reticulum stress suppression in the mouse retina.Materials and methodsAnthocyanins in bilberry extract (100 mg/kg/day or 500 mg/kg/day) were administrated orally to C57BL/6J mice. The expression levels of various molecular chaperones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
0
5
1
3
Order By: Relevance
“…Other than our study on AION, differential regulation of GRP78 and CHOP expression, that is, reduced GRP78 and increased CHOP expression, has been found in RGCs in animal models of optic neuritis and traumatic optic neuropathy 77. Similarly, successful treatment of experimental optic neuropathies and improved RGC survival77,78 have also been associated with differential expression of GRP78 and CHOP in the opposite direction, that is, increased GRP7879 and decreased CHOP expression in cells in the RGC layer. Nakamura et al78 showed that RGC loss after optic nerve crush animal model was associated with decreased GRP78 and increased CHOP expression and that treatment with bilberry extract anthocyanins led to improved RGC survival, increased GRP78 and decreased CHOP expressions, along with reduced expression of BAX and ATF4 , which are downstream of DDIT3 (CHOP).…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Other than our study on AION, differential regulation of GRP78 and CHOP expression, that is, reduced GRP78 and increased CHOP expression, has been found in RGCs in animal models of optic neuritis and traumatic optic neuropathy 77. Similarly, successful treatment of experimental optic neuropathies and improved RGC survival77,78 have also been associated with differential expression of GRP78 and CHOP in the opposite direction, that is, increased GRP7879 and decreased CHOP expression in cells in the RGC layer. Nakamura et al78 showed that RGC loss after optic nerve crush animal model was associated with decreased GRP78 and increased CHOP expression and that treatment with bilberry extract anthocyanins led to improved RGC survival, increased GRP78 and decreased CHOP expressions, along with reduced expression of BAX and ATF4 , which are downstream of DDIT3 (CHOP).…”
Section: Discussioncontrasting
confidence: 49%
“…Similarly, successful treatment of experimental optic neuropathies and improved RGC survival77,78 have also been associated with differential expression of GRP78 and CHOP in the opposite direction, that is, increased GRP7879 and decreased CHOP expression in cells in the RGC layer. Nakamura et al78 showed that RGC loss after optic nerve crush animal model was associated with decreased GRP78 and increased CHOP expression and that treatment with bilberry extract anthocyanins led to improved RGC survival, increased GRP78 and decreased CHOP expressions, along with reduced expression of BAX and ATF4 , which are downstream of DDIT3 (CHOP). Jiang et al77 showed that transplantation of human umbilical cord cells as treatment for traumatic optic neuropathy animal model led to improved RGC survival and increase in expression of GRP78 and decrease in expression of CHOP.…”
Section: Discussionmentioning
confidence: 99%
“…В экспериментальных исследованиях in vitrо и in vivo показано, что активация молекулярных шаперонов способствует сохранению клеток при стрессе ЭПР. В особенности это касается шаперона Grp78, который играет важную роль в ослаблении процесса апоптоза, и шаперона Grp94, подавляющего гибель нейронов при ишемии/реперфузии [9,10]. Эти данные подтверждают, что молекулярные шапероны Grp78 и Grp94 задействованы в защите поврежденных клеток при стрессе ЭПР.…”
unclassified
“…В настоящее время в литературе описаны результаты экспериментального и клинического изучения влияния антоцианозидов экстракта черники на сохранение функциональной активности сетчатки и зрительного нерва при нейродегенеративных заболеваниях [10].…”
unclassified
See 1 more Smart Citation